The Dietary Fats: A Comprehensive Study about the Influence of Different Types of Fats on General Health and Developing Diseases - Sylwia Nykiel; Jagoda Misiuk; Karolina Kopeć; Aleksandra Bartoszek; Julia Adamiuk; Agnieszka Marut; Marta Biskup; Adriana Skuba; Katarzyna Załuska; Agnieszka Świdniak (Quality in Sport)
Introduction and Purpose: One of the main reasons for the increased risk of non-communicable diseases is improper dietary habits. In recent years, studies on the composition and nutritional value of the diet have been intensively developed to establish the relationship between nutrition and the occurrence of diseases. The study presents current knowledge regarding the relationship between the type of fats consumed with food and the risk of all cause mortality, cardiovascular disease, and type 2 diabetes. Materials and Methods: The review is based on a detailed analysis of peer-reviewed studies from major scientific databases such as PubMed. The article is a comprehensive review of current literature, including clinical studies and trials on dietary fats' influence in developing non-infectious diseases and general cardiovascular health. Results: 1)     Saturated fats are not associated with all cause mortality, CVD, CHD, ischemic stroke, or type 2 diabetes, but the evidence is heterogeneous with methodological limitations. 2)     Trans fats are associated with all cause mortality, total CHD, and CHD mortality, probably because of higher levels of intake of industrial trans fats than ruminant trans fats. Dietary guidelines must carefully consider the health effects of recommendations for alternative macronutrients to replace trans fats and saturated fats. Conclusion: It was found that the isomers of trans fatty acids (TFAs) in particular promote the development of coronary heart disease, causing undesirable changes in the blood lipid profile, therefore it is necessary to seek to reduce their content in the diet by limiting the consumption of fats cured by partial hydrogenation of products produced with their use.